How to master negotiation - Carroll, Eileen; Balassa, Balint; Oppenheimer, Leah; Centre for Effective Dispute Resolution (Great Britain) (London : Bloomsbury Professional, 2015)
'How to Master Negotiation' provides individuals with a guide of how to prepare themselves and others for a variety of negotiations - ranging from instantly recognisable transactions, such as deal negotiations, to the more intricate organisational and interpersonal negotiations that often give rise to conflict. How to Master Negotiation provides individuals with a guide of how to prepare themselves and others for a variety of negotiations; ranging from instantly recognisable transactions, such as deal negotiations, to the more intricate organisational and interpersonal negotiations that often give rise to conflict. Over 12 chapters, How to Master Negotiation takes the reader through the concepts and practical skills that a negotiator needs. The book is highly practical with each chapter containing a relevant case study and practical tips in addition to theory and explanation of the concepts.
ContentsChapter 1: Preparing To Prepare: Laying out the roadmap to begin the negotiation process Chapter 2: 'I Could Easily Walk Away, But What Are The Alternatives?': Understanding your options in a conflict negotiation through BATNAs and WATNAs Chapter 3: 'Of Course I Am A Team Player ... They End Up Seeing My Way ... Eventually!': How to prepare your team for a negotiation Chapter 4: 'I Never Let Emotions Get In My Way': Managing your emotions in negotiation Chapter 5: 'I Really Want To Make An Impression': Opening with maximum impact Chapter 6: 'Why Should I Be Flexible When You Are So Difficult?': Moving from your preferred style to an effective strategy Chapter 7: 'But Why Would He Ever Tell Me The Truth?': The impact of trust in negotiation Chapter 8: Avoiding Avoidance: How to negotiate when no one is willing Chapter 9: 'I Know What I Want, So Why Can't You Just Give it To Me?': Identifying positions and interestsChapter 10: 'But I Haven't Done Maths Since School!': Negotiating by the numbers Chapter 11: Whose Line Is It Anyway?: Deploying creativity and improvisation in negotiation Chapter 12: The Road Not Taken: Incorporating reflection, creativity and imagery into your negotiation practice Chapter 13: 'We Are All The Same In The End Aren't We?': Managing cross-cultural negotiationsChapter 14: Conclusion.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Negotiation; Negotiation in business; Negotiating; Négociations.; Négociations (Affaires); Business strategy; Business & management; Arbitration, mediation & alternative dispute resolution; Business negotiation; Business & Economics -- Negotiating; Law -- Alternative Dispute Resolution; Negotiation; Negotiation in business